Meningkatkan Hasil Belajar Matematika Siswa Dengan Memaksimalkan Penggunaan Media Pembelajaran Matematika - La Ode Sirad; Herlina; Arnawati (Arus Jurnal Pendidikan, 2021)
This research is motivated by the desire to know the improvement of student learning outcomes by maximizing the use of mathematics learning media with three-dimensional real objects media. Less interesting learning without the support of effective media and on average students do not like mathematics, causing students' math scores to be low. The low learning outcomes are more visible, especially in abstract subjects that require the use of learning media. The problem studied is "Can maximizing the use of mathematics learning media with three-dimensional real objects media on cubes and blocks material can improve students' mathematics learning outcomes in class VIIIA SMP Negeri 2 Samaturu?". With the action hypothesis, maximizing the use of mathematics learning media with three-dimensional real objects on cubes and blocks can improve mathematics learning outcomes for class VIIIA students of SMP Negeri 2 Samaturu. This research is a Classroom Action Research (CAR) conducted in collaboration between teachers, observers and researchers with research procedures that include planning, implementation, observation and reflection. The subjects studied were students in class VIIIA with a total of 29 students. The types of data obtained are qualitative data and quantitative data which are analyzed qualitatively and quantitatively. The results obtained by referring to the Minimum Completeness Criteria (KKM), namely at least 75% of students have obtained a minimum score of 70. In the first cycle of action evaluation, classical completeness was 55.17% with an average value of 69.44. After the evaluation of the second cycle of action, the classical completeness achieved was 86.21% which obtained a score of 70 with an average value of 82.86. So it can be concluded that by maximizing the use of learning media with three-dimensional real objects media can improve mathematics learning outcomes for class VIIIA students of SMP Negeri 2 Samaturu.